Enjoyable econometrics - Franses, Philip Hans, 1963- (New York : Cambridge University Press, 2018)
"Econometrics can at first appear a highly technical subject, but it can also equip the practitioner with a useful skillset of smart ways to formulate research questions and collect data. Enjoyable Econometrics applies econometric methods to a variety of unusual and engaging research questions, often beyond the realm of economics, demonstrating the great potential of using such methods to understand a wide range of phenomena. Unlike the typical textbook approach, Enjoyable Econometrics follows in the footsteps of Freakonomics by posing interesting questions first before introducing the methodology to find the answers. Therefore, rather than equation-heavy sections based around complex methodologies, the reader is presented with chapters on 'Money' and 'Fashion, Art and Music'. Franses writes in a way that will enthuse and motivate the economics student embarking upon the essential study of econometrics. Indeed, the book shows that econometric methods can be applied to almost anything"--
"Pleasure in the job puts perfection in the work" Aristotle At a glance This book deals with applications of econometric methods and techniques to a variety of questions, often and on purpose outside the realm of economics. Usually, econometric methods are considered for questions in macroeconomics, labor economics or finance, among others. However, admittedly, when you are a novice to the field, the examples and illustrations in econometric textbooks may not be that entertaining, and hence the very fact that illustrations are chosen as such, may reduce your wish to master the methods yourselves. Well, in plain English, several examples in textbooks do not look very challenging"--
Keywords: Econometrics; Econometrics -- Popular works